Impact of US embargo on trade-flows between the United States and the Republic of Cuba - Soročinová, Viktória; Chytilová, Helena; Prokop, Jaromír; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2018)
The main topic of the bachelor thesis is the impact of the U.S. embargo on the Republic of Cuba. The main hypothesis is an analysis of the embargo on the trade-flows between these two countries. Results of the regressions and data analysis were not able to prove the main hypothesis. Nevertheless, graphical analysis provided information about the negative impact of the embargo for both countries. One of the conclusions is that the United States mistreat one of the most profitable lines of its import not only from the geographical point of view, but also in terms of specialization. In order to verify hypothesis, we used three OLS regressions, which are using data collected by the Knoema search engine for the data. Furthermore, our investigation was backed by thorough graphical and historical analysis of their relationship and economic influence of the embargo. Methodology was taking its inspiration from the examination of gravity models (Hufbauer-Oegg, 2003; Bosco-Lionetti, 2015).
Vedoucí práce: Helena Chytilová
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: economics [obor bakal. práce]; bakalářské práce; bachelor's theses